Propagation of chaos for topological interactions - Degond,P; Pulvirenti,M (Annals of Applied Probability, 2019)
We consider aN-particle model describing an alignment mechanism due to a topolog-ical interaction among the agents. We show that the kinetic equation, expected to holdin the mean-field limitN→∞, as following from the previous analysis in Ref. [3] can berigorously derived. This means that the statistical independence (propagation of chaos)is indeed recovered in the limit, provided it is assumed at time zero.